치위생과정에 기반한 임상치위생학 교육과정 역량 개발을 위한 타당도 평가 - 최진선; Jin-sun Choi; 신선정; Sun-jung Shin; 신보미; Bo-mi Shin; 이효진; Hyo-jin Lee; 윤혜영; Hye-young Yoon; 배수명; Soo-myoung Bae (Han'guk Ch'iwisaeng Hakhoe chi, 2024)
Objectives: Before implementing a competency-based clinical dental hygiene curriculum, it is essential to establish competency development as a foundational educational objective. Therefore, this study aimed to develop the competency of clinical dental hygiene with secured validity using the Delphi survey method. Methods: Dental hygiene competencies were categorized within the dental hygiene process stages, and questions were formulated accordingly. A Delphi survey involving ten qualified experts was conducted to refine the final items based on their review opinions. Results: The expert Delphi survey confirmed that all items met stability criteria, with CVI values of 0.80 or higher, CVR values of 0.60 or higher, and a CV coefficient of variation of 0.5 or less. In total, 42 items were derived. Conclusions: Clinical dental hygiene can contribute to developing specialized dental hygienists if the competencies derived from this study are well applied to the standardized curriculum and operations.